Pengaruh Pendekatan PMR (Pendidikan Matematika Realistik) terhadap Kemampuan Berpikir Kreatif Siswa Kelas VIII SMPN 3 Muara Batang Gadis - Mhd. Afni; Nurdalilah; Harahap, Adek Nilasari (Journal Education Innovation (JEI), 2025)
This study aims to determine the effect of the application of Realistic Mathematics Education (PMR) approach on the creative thinking ability of VIII grade students at SMPN 3 Muara Batang Gadis. The research used quasi-experiment method with Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the experimental class that received treatment with the PMR approach and the control class that received conventional learning. Data were collected through a mathematical creative thinking test that included four indicators: fluency, flexibility, originality, and elaboration. The analysis showed that there was a significant difference between the average posttest scores of the experimental (80.2) and control (70.4) groups, with a t-test result of 6.33 and a p-value of 0.000. In addition, the scores on each creative thinking indicator were higher in the PMR group than the control group. This shows that the PMR approach is able to improve students' creative thinking skills as a whole. PMR-based learning encourages students to think more flexibly, creatively, and be able to connect math concepts with real life. Thus, PMR can be an effective alternative learning model in improving the quality of mathematics learning in secondary schools.